Endocannabinoid-Dependent Homeostatic Regulation of Inhibitory Synapses by Miniature Excitatory Synaptic Activities - Zhang, Si-yu (Society for Neuroscience, 2009)
Homeostatic regulation of synaptic strength in response to persistent changes of neuronal activity plays an important role in maintaining the overall level of circuit activity within a normal range. Absence of miniature EPSCs (mEPSCs) for a few hours is known to cause upregulation of excitatory synaptic strength, suggesting that mEPSCs contribute to the maintenance of excitatory synaptic functions. In the present study, we found that the absence of mEPSCs for 1–3 h also resulted in homeostatic suppression of presynaptic functions of inhibitory synapses in acute cortical slices from juvenile rats, as suggested by the reduced frequency (but not amplitude) of miniature IPSCs (mIPSCs) as well as the reduced amplitude of IPSCs. This homeostatic regulation depended on endocannabinoid (eCB) signaling, because blockade of either the activation of cannabinoid type-1 receptors (CB1Rs) or the synthesis of its endogenous ligand 2-arachidonoylglycerol (2-AG) abolished the suppression of inhibitory synapses caused by the absence of mEPSCs. Blockade of group I metabotropic glutamate receptors (mGluR-I) also abolished the suppression of inhibitory synapses, consistent with the mGluR-I requirement for eCB synthesis and release in cortical synapses. Furthermore, this homeostatic regulation also required eukaryotic elongation factor-2 (eEF2)-dependent protein synthesis, but not gene transcription. Activation of eEF2 alone was sufficient to suppress the mIPSC frequency, an effect abolished by inhibiting CB1Rs. Thus, mEPSCs contribute to the maintenance of inhibitory synaptic function and the absence of mEPSCs results in presynaptic suppression of inhibitory synapses via protein synthesis-dependent elevation of eCB signaling.